Gambaran Perilaku Bullying Remaja di SMA Stella Gratia Atambua - Djulianus Tes Mau; Elvira Trivony Kolo (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Bullying is an aggressive act carried out calmly without burden, deliberately and repeatedly to attack a target or victim, who is specifically someone who is weak, easily teased and unable to defend themselves. Bullying can be caused by socio- cultural factors and also family factors. This research aims to find to find out how bullying behavior is described in teenagers at Stella Gratia Atambua High School. The method used in this research is quantitative descriptive to see the picture of bullying behavior among teenagers at Stella Gratia Atambua High School. The population in this study is 268 students at Stella Gratia Atambua High School the sample of this research is 160 people with a side positive sampling technique. The instrument used in this research is olweus bully/victim questionare revised which has been carried out in a validity test. The result of research conducted at show that the level bullying behavior, show that the level of bullying behavior is in the low category as many as 158 respondents (98,75%).